Dua Bagian Roh: Tanggung Jawab Profetik Elisa terhadap Allah dalam Mengemban Misi - Agustinus Ruben; Nelvi Datu Rombe (Voice, 2024)
The purpose of this paper is to explain the biblical study of the responsibility of a leader named Elisha. The research method used is qualitative research method. Responsibility has the purpose of expressing the importance of the desire to lead and even continue a ministry that is expected to lead God's people with power and wisdom. Elisha was called to a tremendous prophetic responsibility in his journey of serving God and His people. This responsibility is not just about fulfilling a task, but it has a deeper purpose of expressing the importance of sincere desire in spiritual leadership. The responsibility that lies within a person should be a moment to continue to develop integrity and passion. A person needs to understand himself in his responsibility that there are limitations and even inability, and with this awareness man can focus the responsibility on the highest authority, namely Jesus Christ who will be the center of help. Thus man is able to step forward in leading God's people as evidence of this responsibility.